Improvement of Gayo Lues Patchouli Oil Alcohol Quality With Absorbent Variations of Juice And Purut Orange Peel (Citrus hystrix) - Vera Viena; Elvitriana Elvitriana; Zulhaini Sartika; Diana Patra (Serambi Journal of Agricultural Technology, 2020)
Patchouli oil refinery in Gayo Lues Aceh Indonesia commonly used evaporation process in an old drums at high temperature which decreased the quality of oil produced. The research to enhance the quality of patchouli alcohol of Gayo Lues patchouli oil using Citrus hystrix absorber has been done.The juice from kaffir lime (1 – 10 % v/v) used as chelating agent, and the kaffir peels powder (2,5 - 7 gr) used as bio sorbent. The highest patchouli alcohol (P.A) both resulted at T=50 oC and 60 minutes heating. Kaffir bio sorbent at 7,5 gr usage, gave 40,37% P.A and Fe reduction of 77,67%; while kaffir lime juice at 4% v/v usage, gave P.A 39,90% and Fe reduction of 78,25%. Purified patchouli oil also characterized by its light yellow color, density and refractive index based on SNI.06-2385-2006. It’s concluded that kaffir peels bio sorbent purification has superior P.A quality than kaffir lime juice.